2017
DOI: 10.5194/acp-17-7387-2017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of North America on the aerosol composition in the North Atlantic free troposphere

Abstract: Abstract. In the AEROATLAN project we study the composition of aerosols collected over ∼ 5 years at Izaña Observatory (located at ∼ 2400 m a.s.l. in Tenerife, the Canary Islands) under the prevailing westerly airflows typical of the North Atlantic free troposphere at subtropical latitudes and midlatitudes. Mass concentrations of sub-10 µm aerosols (PM 10 ) carried by westerly winds to Izaña, after transatlantic transport, are typically within the range 1.2 and 4.2 µg m −3 (20th and 80th percentiles). The main … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 60 publications
4
17
0
Order By: Relevance
“…During Saharan dust events, PM 10 concentrations increased from the background level to values within the ranges 35-50 µg/m 3 (during "moderate" events), 50-100 µg/m 3 ("intense") and 100-400 µg/m 3 ("very intense"; Figure 2A). In these cases, PM 10 was, by far, constituted by mineral dust [29,30] (see the typical ochre colour and the chemical composition of PM 10 samples during these events in Figure 3).…”
Section: Dust Eventsmentioning
confidence: 99%
“…During Saharan dust events, PM 10 concentrations increased from the background level to values within the ranges 35-50 µg/m 3 (during "moderate" events), 50-100 µg/m 3 ("intense") and 100-400 µg/m 3 ("very intense"; Figure 2A). In these cases, PM 10 was, by far, constituted by mineral dust [29,30] (see the typical ochre colour and the chemical composition of PM 10 samples during these events in Figure 3).…”
Section: Dust Eventsmentioning
confidence: 99%
“…The site is located above the inversion layer typical of the subtropical region. Izaña is exposed to the westerly winds typical of the North Atlantic (García et al, 2017a), except in summertime, when it is impacted by the dusty Saharan Air Layer (Rodríguez et al, 2015). At night, anticyclonic subsidence and unperturbed free conditions prevails at Izaña, whereas during daylight upslope winds occurs, resulting in the transport of some local aerosol precursor liked to anthropogenic and biogenic sources and new particle formation events (García et al, 2014;García et al, 2017b;Rodríguez et al, 2009).…”
Section: Measurement Site Descriptionsmentioning
confidence: 99%
“…However, there is little consensus about which lidar ratio is more appropriate for this aerosol type. Groß et al (2013) performed a comprehensive analysis on the different lidar ratios reported in prior studies for pure desert Saharan dust. They found very different values, ranging between 40 and 70 sr and set a value of 48±5 sr by means of airborne lidar observations.…”
Section: Introductionmentioning
confidence: 99%